(untitled) (Journal of Academic Research, 2023)
This study aimed to demonstrate the effect of the dimensions affecting the transformation behavior of the clients of the Libyan commercial banks, as well as an attempt to identify the most important differences in the responses of the respondents about the dimensions affecting the transformation behavior of customers in the banks under study, where the problem of the study lies in answering the following question: What are the dimensions affecting the transformation behavior of the clients of the Libyan commercial banks? Are there statistically significant differences in the averages of the answers of the study sample regarding the study of the dimensions affecting the transformation behavior of the bank customers under study due to some personal variables (age - gender - educational qualification)? The study used the descriptive analytical method. Considering the appropriate approach to achieve its objectives, and considering that the study population is not specified, the researcher sent the questionnaire form electronically via Facebook groups to commercial banks operating within the scope of the municipality of Qasr Al-Akhyar. Its purposes, which are represented in some measures of central tendency such as the arithmetic mean, the weighted arithmetic mean, the standard deviation, some frequency distributions, the Alpha Cro-Nabach coefficient for stability, the validity of structural consistency, and the (One Sample T-test) test in order to find out the dimensions affecting the transformation behavior of clients The commercial banks under study. The study reached a set of results, the most important of which are: The level of influence of the dimensions affecting the transformation behavior of customers in the banks under study was high, except for the level of the cost of transformation, which was medium, from the point of view of the study sample.